2022
DOI: 10.1021/acsami.2c03796
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized-MXene Thin-Film Nanocomposite Hollow Fiber Membranes for Enhanced PFAS Removal from Water

Abstract: Due to adverse health effects and the broad sources of per-and polyfluoroakyl substances (PFAS), PFAS removal is a critical research area in water purification. We demonstrate the functionalization of thin-film composite (TFC) hollow fiber nanofiltration (HFN) membranes by MXene nanosheets during the interfacial polymerization (IP) process for enhanced removal of perfluorooctane sulfonic acid (PFOS) from water. A MXenepolyamide (PA) selective layer was fabricated on top of a polysulfone (PSF) hollow fiber supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…In the case of PFAS removal via an adsorption-based process coupled with membranes, the membrane’s surface is coated with adsorbent materials and the process is controlled by the characteristics of adsorbents, such as adsorbent particle size, surface area, pore-volume, etc. In such cases, the electrostatic force between the membrane surface and the PFAS mostly depends on the adsorbent material and not the membrane’s properties [ 112 ].…”
Section: Factors Controlling Pfas Separation By Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of PFAS removal via an adsorption-based process coupled with membranes, the membrane’s surface is coated with adsorbent materials and the process is controlled by the characteristics of adsorbents, such as adsorbent particle size, surface area, pore-volume, etc. In such cases, the electrostatic force between the membrane surface and the PFAS mostly depends on the adsorbent material and not the membrane’s properties [ 112 ].…”
Section: Factors Controlling Pfas Separation By Membranesmentioning
confidence: 99%
“…Functionalized-MXene (Ti 2 C 3 T x , 0–0.05 wt% MXene) thin-film nanocomposite hollow fiber membranes ( Figure 9 ) were successfully developed by Le et al, for PFOS removal from water. The thin film was formed through interfacial polymerization [ 112 ], and the coated polyamide-MXene layer (optimum at 0.025 wt% MXene) on polysulfone hollow fiber support was able to increase PFOS rejection from 72 to 96% in comparison to a PES polyamide hollow fiber. Furthermore, the addition of an MXene layer increased the permeability from 13.9–29.26 LMH/bar.…”
Section: Novel Membranes For Pfas Rejection and Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…32 And Milad et al demonstrated one composite MXene hollow fiber membrane using an interfacial polymerization method. 33 However, the random distribution of MXene nanosheets in membranes could increase the molecular transport resistance. To better control the interlayer spacing, dip-coating is a viable technology for fabricating conformational 2D hollow fiber membranes, since the film thickness can be well regulated by controlling the coating speed and cycles, which can achieve a precise selective layer with controlled configurations (thickness or structures).…”
mentioning
confidence: 99%
“…For MXene membranes based on a polymeric support, Zhang et al designed one hydrophobic–hydrophilic MXene/PVDF hollow fiber membrane using a chemical grafting method . And Milad et al demonstrated one composite MXene hollow fiber membrane using an interfacial polymerization method . However, the random distribution of MXene nanosheets in membranes could increase the molecular transport resistance.…”
mentioning
confidence: 99%